(untitled) - Velte, Toby J (Berkeley, California, 2000)
This book covers a variety of topics that are inportant the those designing, building, and maintaining networks with Cisco and Microsoft products. It contains four major section. The first discusses Cisco and Windows convergence; the second explains the nuts and bolts of building networks; the third focuses on managing a network once you've built it; and the fourth outlines strategies you can use to connect others to your network.
Keywords: client/server computing,microsoft windows NT,network computing,operating system,system administration